Drug effectiveness reporting and monitoring systems: discussion and prototype development. (27th March 2009) - Gupta, Amar; Crk, Igor; Sarnikar, Surendra; Karunakaran, Bipin
While tracking systems have been developed to decrease occurrences and consequences of medication errors in healthcare facilities, there is a growing need for similar systems to monitor drugs that have just entered the market with unknown adverse events. Between 1997 and 2005, the FDA's MedWatch system successfully identified 15 drugs with toxic side-effects; it took an average of 5.9 years for identification and removal of such drugs. We propose an online surveying system, coupled with continuous monitoring by participating pharmacists, that could significantly reduce the identification time and the removal time. Further, we analyse the potential for leveraging advances in semantic web and ontology development to populate the database of the proposed system.